PERAN KEPALA KUA DALAM MENYELESAIKAN PERMASALAHAN SURAT PENOLAKAN NIKAH PERSPEKTIF KOMPILASI HUKUM ISLAM (KHI) PASAL 53 AYAT 1 (STUDI KASUS KUA KECAMATAN BATU KOTA BATU) - Lidia Sandy Kartika; Ach. Faisol; Shofiatul Jannah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Basically, marriage is mitssaqan ghalidzan, namely to obey Allah's commands and carry it out is a worship because marriage is recommended in Islam. O¹f course, life cannot be created perfect, like teenagers who are still looking for identity in their world, many are carried away by the current so that they fall into a gloomy abyss, cannot carry themselves because of the lack of faith in every step they take. Therefore, worship to strengthen our faith and devotion to Allah SWT is very important, so it should be instilled early on. Like the case in Batu City KUA, the Head of KUA refused to issue a marriage refusal letter. There is a policy regarding refusing to issue a marriage refusal letter because the woman is pregnant, so the Head of KUA Kota Batu postpones marriage until she gives birth. The policy of the Head of KUA Kota Batu was determined because this policy had existed since the first Head of KUA Kotab Batu was still on duty at KUA Junrejo in 2010, of course there was a purpose for the policy so that it was still applied at KUA City and the policies taken had a legal basis in terms of some legal grounds that strengthen the case such as the understanding of the Imam Hambali School forbidding to marry a pregnant woman because a pregnant woman does not have a mass iddah until she gives birth. Kata Kunci: Marriage Rejection Letter, Islamic Law, Pregnant Women